Regenerative Medicine’s Current State of Affairs - Halwai, Hemant Kumar (Journal of Universal College of Medical Sciences, 2022)
The basic concept behind tissue engineering is to recreate existing surgical or mechanical device-related procedures, even if those procedures greatly reduced the rate of untimely death. The phrase "Tissue Engineering" (TE), coined in 1933 by Langer and Vacanti, refers to the time-on-demand of available organ donors and suitable complementary biological habitats. TE is the multifaceted product of researchers that have significantly modified and recreated the in vivo biological niche using a combination of synthetic biomaterials, cells of interest, and biochemical components, which are crucial for tissue growth. The disciplines of regenerative medicine have been transformed by the new generation of biomaterials, and the advancement of 3D architecture may allow us to replicate the perfect in vivo tissue organoid.